Simulação de algoritmos quânticos considerando a teoria quântica modal em Haskell - Silva, Eduardo Ferreira da (2014)
The development of quantum algorithms faces some difficulties such as the lack of a general-purpose quantum computer, a language or a specific formalism, or high consumption of computational resources when it is simulation of quantum algorithms on classical computers. This paper presents the development of the MQS (Modal Quantum Simulatio), a library of quantum computing written in Haskell able to develop implementation of algorithms considering the Quantum Theory Modal. This theory is attractive as the replacement of complex probability amplitudes for finite fields. A simplified theory is compared with the conventional quantum computing, but retains much of the structure of the traditional quantum computing.